Shaping the future of accounting in business education in Australia - O'Connell, B.; Carnegie, G.; Carter, A.; de Lange, Paul; Hancock, P.; Helliar, C.; Watty, K. (2015)
This multi-stakeholder investigation with a prospective focus and conducted 25 years after the Mathews Committee Inquiry has three aims: ? assess the current state of play of accounting in business education in Australia; ? focus on the key challenges, issues and opportunities faced by the accounting education sector; and ? develop feasible, innovative and productive ways forward to meet the many challenges faced by accounting education and to take full advantage of the opportunities identified. The key themes embraced in the investigation are as follows: professional knowledge and professional skills of accounting graduates; the inculcation of professional values, ethics and attitudes into graduates; scholarly research and its role in accounting education, creating knowledge and informing practice; and technology and innovation in learning environments. This study presents the findings drawn from interviews with individuals who are engaged actively in graduate recruitment and the ongoing professional development of accountants. These interviewees were drawn from four key stakeholder groups comprising small, medium and large professional services firms, other employers of accounting graduates, regulators, including the major professional accounting bodies, and accounting academics. The key findings indicate that the future of accounting, like other facets of society, is being transformed by technology and the future of accounting work will advance into new areas while retaining broadly its fundamental core knowledge areas. New entrants into this field will need to possess well developed professional skills on their entry into the profession and, in combination with evolving professional knowledge and a solid core of professional values, ethics and attitudes. In addition, they need to have an ability to create value as business and wealth advisors, interpreters and communicators of financial and non-financial information, and contribute to the strategic direction of organisations, in particular, and society, in general. The findings of this investigation have resulted in the development of 17 recommendations designed to provide proactive strategies to meet the challenges presented and these are provided for higher education providers and accounting schools, employers, professional accounting bodies, and accounting students. While the main recommendations relate to accounting curricula and connections between academe and the profession, it is proposed that an Accounting Education and Curriculum Change Network be established to oversee any reforms, administered by the major professional accounting bodies with AFAANZ, and having membership drawn from higher education providers around Australia. For accounting education this presents new and exciting challenges as curricula are transformed by key enabling technologies and the new realities of the profession in an increasingly globalised world. Programs and degrees will incorporate more real world experience and academics, by engaging more directly with professional practice through both teaching and research, will become cognisant of their instrumental formative role in the initial professional development of accountants. Studying accounting in the contexts in which it operates as technical and social practice will assist in facilitating improved educational experiences and outcomes.